Forensic age estimation in living subjects based on the ossification status of the medial clavicular epiphysis as revealed by thin-slice multidetector computed tomography - Kellinghaus, Manuel; Schulz, Ronald; Vieth, Volker; Schmidt, Sven; Schmeling, Andreas (International journal of legal medicine, 2010)
Determination of the stage of ossification of the medial clavicular epiphysis is a crucial part of age estimation in criminal proceedings when evaluating individuals with completed hand ossification. In order to ensure a maximum of accuracy in forensic age estimation practise, it is recommended to perform thin-slice CT scans; but to date there exist no reference data on the bone development of the region in question based on thin-slice computed tomography. In this retrospective study, the authors evaluated thin-slice multidetector CT images of 592 individuals aged between 10 and 35 years produced in the University Hospital of Münster. The ossification status of the medial epiphysis of the clavicle could be reliably determined in 502 cases using the classification of stages by Schmeling et al. In male individuals, stage 2 was first noted at age 14, in female individuals at age 13. Stage 3 was first achieved by male individuals at age 17, by female individuals at age 16. The occurrence of stage 4 was first found in both sexes at the age of 21. In either sex, the earliest observation of stage 5 was at age 26. The findings are basically in line with those from the only CT-based study on the subject in question using the same classification of five stages, except from the fact that in the present study, stage 5 first occurs at age 26, which is 4 or 5 years later than what was found in the CT study using 7 mm slices in the majority of cases. This vast difference may be explained through the partial volume effect occurring with thick-slice CT images by a visual deception of the epiphyseal scar occurring with stage 4.